GC/MS Profiling and Biological Traits of Eucalyptus globulus L. Essential Oil Exposed to Solid Lipid Nanoparticle (SLN). Issue 4 (4th July 2021) - Azadmanesh, Roohollah; Tatari, Maryam; Asgharzade, Ahmad; Taghizadeh, Seyedeh Faezeh; Shakeri, Abolfazl
Abstract: Nanotechnology has contributed to the development of new botanical formulations based on essential oils (EOs), which are safe for human health and the environment. The present study was conducted to determine the effects of Solid Lipid Nanoparticles (SLN) on the chemical and biological efficacies of Eucalyptus globulus EO (EGEO). Chemical composition was quantified by chromatography-mass spectrometry (GC/MS). Also, the cytotoxic, antimicrobial, and antifungal efficacies of the EGEO and EGEO-loaded SLN were assessed against eight cell lines, eight bacterial strains, and two fungi strains, respectively. SLN significantly increased the EGEO yield and the level of phytoconstituents. GC/MS analysis of EGEO chemical composition exposed 35 components in EGEO accounting for 99.4 and 86.9 % of EGEO-loaded SLN, respectively. In EGEO and EGEO-loaded SLN samples, the major components were 1, 8-Cineol (68.1 and 74.3 %, respectively) and α-pinene (15.0 and 17.3 %, respectively). The nanoparticles significantly decreased the minimum bactericidal concentration (MBC), minimum inhibitory concentration (MIC), and minimum fungicidal concentration (MFC) of EGEO. The nano-lipo encapsulation significantly enhanced the cytotoxic effect of EGEO. Therefore, nanocapsules may be regarded as an interesting strategy for improving EOs stability and biological efficacy.